Mycelium-based biomaterials as smart devices for skin wound healing - Ruggeri, Marco; Miele, Dalila; Contardi, Marco; Vigani, Barbara; Boselli, Cinzia; Icaro Cornaglia, Antonia; Rossi, Silvia; Suarato, Giulia; Athanassiou, Athanassia; Sandri, Giuseppina (Frontiers in Bioengineering and Biotechnology, 2023)
Recently, mycelia of Ganoderma lucidum and Pleurotus ostreatus, edible fungi, have been characterized in vitro as self-growing biomaterials for tissue engineering since they are constituted of interconnected fibrous networks resembling the dermal collagen structure. This work aims to investigate the biopharmaceutical properties of G. lucidum and P. ostreatus mycelia to prove their safety and effectiveness in tissue engineering as dermal substitutes. The mycelial materials were characterized using a multidisciplinary approach, including physicochemical properties (morphology, thermal behavior, surface charge, and isoelectric point). Moreover, preclinical properties such as gene expression and in vitro wound healing assay have been evaluated using fibroblasts. Finally, these naturally-grown substrates were applied in vivo using a murine burn/excisional wound model. Both G. lucidum and P. ostreatus mycelia are biocompatible and able to safely and effectively enhance tissue repair in vivo in our preclinical model.